School as a political agent: the formative and recurring role of schools in society - Valeria Angelini (Firenze University Press, 2023)
The paper aims to explore the political role of schools and the importance of democratic education in the contemporary context. Education is a crucial factor in shaping future generations for change in societies. School, as a central institution in the educational process, plays a fundamental role in promoting democratic values and providing individuals with the necessary skills to actively participate in political life. It takes a critical and reflective perspective on the political role of schools and the importance of democratic education for the development of more inclusive, balanced and democratic societies.   La scuola come agente politico: il ruolo formativo e ricorrente della scuola nella società. Il contributo si propone di esplorare il ruolo politico della scuola e l'importanza dell'educazione democratica nel contesto contemporaneo. L'educazione è un fattore cruciale nella formazione delle future generazioni per il cambiamento delle società. La scuola, come istituzione centrale nel processo educativo, svolge un ruolo fondamentale nel promuovere valori democratici e fornire agli individui le competenze necessarie per partecipare attivamente alla vita politica. Si pone come una prospettiva critica e riflessiva sul ruolo politico della scuola e sull'importanza di un'educazione democratica per lo sviluppo di società più inclusive, equilibrate e democratiche.